TEACHING INTEGRATING DIGITAL INSTRUMENTS INTO ELT - Tursunboyeva Majudakhon Shukrillo qizi (Modern American Journals, 2025)
With the development of ICT, a large number of instructional programs and educational platforms have been created. When technology and English teaching are combined, students have the most engaging and productive language learning experience. The best method for gaining proficiency and fluency is through the use of technology in language acquisition. This article explores the benefits of using digital resources in university courses that teach English as a second language.
Keywords: Higher education, pupils, English teaching, learning platforms, digital tools, and ICT